The new nomads : temporary spaces and a life on the move - Ehmann, Sven; Klanten, Robert; Galindo, Michelle; Borges, Sofia (Gestalten, 2015)
Mobility is the ultimate new form of freedom: freedom from routine, traditional values, and geographic restraints. Today's creatives thrive on a lifestyle that enables them to work six months in a shared office in Berlin, spend the summer in a caravan in Chile, and show up in time for their next project at a temporary desk in New York. This growing trend has generated visionary ways of designing products and spaces that facilitate a nomadic yet high-tech life. From a modular dwelling system on wheels to an inflatable classroom in a repurposed dumpster, this book compiles a wide range of flexible spaces and innovative products that define today's nomads. Through innovative technology, and by (literally) thinking outside the box, the designers behind these concepts give people the freedom to call the entire world their home. The New Nomads documents this trend, in particular showing the architecture, interior design, modular furniture, and multi-functional tools that this nomadic generation has developed for its own specific needs. Divided office floors with flexible uses, temporary living and working spaces that move with the nomads, multi-functional objects that are at once chair and storage space, table and bed, or cupboard and desk are all featured in the book. The necessary infrastructure is not hidden away but becomes the distinguishing design feature. Compactness and functionality meet a high standard for aesthetics, sustainability, and material. Representatives of this nomadic generation can be found across the globe. They leave traces, especially in major cities but also in transportation hubs. The sleeping pod at the airport is booked on short notice due to cancelled connecting flights. Desks, meeting rooms, showrooms, and catering are available for a few hours or days at a time if necessary. Experimental thinkers develop mobile units that can be used in conjunction with existing infrastructures or on their own. Putting down roots now means acquiring a weekend abode, a community garden, or a tree house. Through these innovative types of room concepts and furniture, a multi-functional temporary living space becomes a nomadic home. What might currently be perceived as an exception is, in fact, rapidly becoming the rule. The New Nomads explores a phenomenon that is already starting to make an impact on the work of architects, city planners, product designers, and employers worldwide